Materiais para aplicações eletroquímicas: otimização da síntese de grafeno/TiO2-RuO2 e estudo da retificação de corrente iônica em nanoporos - Silva, Mariana Cristina (Universidade Federal de São Carlos, 2020)
The current energy outlook points to the need to implement methodologies that value the reduction of energy consumption, as well as the use of cleaner and more sustainable processes of production, conversion, and storage of energy. In this scenario, there is a need for a deeper understanding of phenomena and materials involved in energy-related applications. In this sense, the first part of this thesis focuses on the study of microwave-assisted hydrothermal synthesis and characterization of graphene oxide decorated with RuO2 and TiO2 nanoparticles. The selection of this material for the study is due to its potential application in the development of energy storage devices. Several parameters were studied: relative amount of metallic precursors, synthesis medium, pH, starting reactants, composition, and temperature. Among these variables, the effect of pH should be highlighted: at extremely acidic pH (pH<0), there is no formation of RuO2 particles; at slightly basic pH (pH 8), the forced hydrolysis of metallic precursors leads to the formation of amorphous oxides and hydroxides agglomerates; at slightly acidic pH (pH 4) – and changing the Ti4+ precursor so that it is soluble at this pH –, particles with an average size of 18 nm are obtained, and the presence of ruthenium can be confirmed. Still in the context of energy-related theme, the second part of this thesis deals with the study of the phenomenon of ionic current rectification in nanopores. This understanding of basic concepts is fundamental to the systems improvement, as it leads to the possibility of optimizing processes and, therefore, lower energy consumption. To help understand the phenomenon, this thesis used mathematical and computational tools to study the effect of ionic current rectification in nanopores through finite element simulation. This rectification effect can be used as a basis for the construction of several devices since they work in the storage of potential energy. Based on experimental evidence, pore geometry, dimensions and surface charge were studied. Through this study it became clear the need for the pore to present asymmetry, nanometric dimensions and surface charge for the current rectification effect to occur. In this sense, it was evident that the greater the charge and the smaller the opening on one side of the pore, the greater the current rectification observed. Through factorial design, it was possible to observe that the pore narrowing dimension is a significant parameter in the values of rectification ratio, as expected due to the importance of the Debye length in these cases.
Materials for electrochemical applications: optimization of the synthesis of graphene/TiO2-RuO2 and study of ionic current rectification in nanopores
Keywords: Síntese hidrotérmica; Grafeno; TiO2; RuO2; Micro-ondas; Retificação de corrente; Nanoporos; Elementos finitos; Microwave-assisted; Hydrothermal synthesis; Graphene; Current rectification; Finite element method; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::QUIMICA DE INTERFACES